Strategi Pemasaran Depot Air Minum Isi Ulang Barito Dalam Meningkatkan Penjualan di Desa Baru Kecamatan Batang Kuis - Rendi Prayoga; Habib Bayhaqi; Muhammad Al Fazri; Zainarti . (LPPM IAI Nasional Laa Roiba Bogor, 2023)
A corporation may use marketing strategy to thrive in the face of fiercer and fiercer competition by offering the greatest goods and services to satiate its clients and foster strong brand loyalty. This paper was written with the intention of identifying the marketing approach used by the Barito replenish drinking water depot to boost sales in Baru Village, Batang Kuis District. This essay was written using qualitative research that took a descriptive stance. In the meanwhile, the author employed the techniques of observation, interviewing, and literature study. Primary data and secondary data were the sources of the data used in this study. Based on the findings of the analysis, it can be said that the Barito refill drinking water depot employed the proper marketing strategy under the marketing mix approach to win over clients, namely by implementing strategies for both product, price, distribution, and promotion that were carried out correctly target and in accordance with the desired target. Keyword: Marketing Strategy, Sales, Barito Refill Drinking Water Depot Business